2015
DOI: 10.1039/c5tc02295a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aliovalent doping on the properties of perovskite-like multiferroic formates

Abstract: We report synthesis, thermal, dielectric, Raman, IR and luminescence studies of chromiumdoped multiferroic MOF, [(CH 3 ) 2 NH 2 ][Mn(HCOO) 3 ] (DMMn). These studies reveal that doping with chromium(III) leads to lowering of the ferroelectric phase transition temperature T c . The doping also changes the character of the phase transition from strongly first-order for undoped sample to partially diffused one for 3.1% of chromium doping. This behavior resembles behavior of inorganic ABO 3 perovskite ferroelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 52 publications
5
56
0
Order By: Relevance
“…It has been recently demonstrated that aliovalent doping of DMMnF with Cr(III) can be used to tune the magnetic and dielectric properties of these compounds. On the other hand, the present work shows that these properties can be tuned on the basis of particle size and morphology, as opposed to compositional tuning . Finally, we emphasize the increased importance of inter‐particle interactions at small sizes, which results in magnetic as well as dielectric relaxor‐like behavior below average particle size ∼1 μm, demonstrating the use of size‐confinement to obtain a functionally and fundamentally interesting property in these materials.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…It has been recently demonstrated that aliovalent doping of DMMnF with Cr(III) can be used to tune the magnetic and dielectric properties of these compounds. On the other hand, the present work shows that these properties can be tuned on the basis of particle size and morphology, as opposed to compositional tuning . Finally, we emphasize the increased importance of inter‐particle interactions at small sizes, which results in magnetic as well as dielectric relaxor‐like behavior below average particle size ∼1 μm, demonstrating the use of size‐confinement to obtain a functionally and fundamentally interesting property in these materials.…”
Section: Introductionmentioning
confidence: 57%
“…This behavior has been previously reported in ABX 3 MOFs. However, it was obtained either by introducing disorder in the form of mixed‐valence B ions, i.e., aliovalent doping of the divalent MOFs or by slowing down the molecular dynamics using deuterated A ions . Below, we show evidence of this behavior in micron‐sized particles of the MOF DMMnF.…”
Section: Resultsmentioning
confidence: 83%
“…The known formates have been extensively studied in a broad temperature range, and these studies showed that majority of them undergo phase transitions associated with orientational ordering of organic cations located in the cavities of the framework . Pressure is another thermodynamic parameter that can help to better understand structure–property relationship in this class of compounds .…”
Section: Introductionmentioning
confidence: 99%
“…The nature of this ferroelectric transition has been probed using several techniques such as electrical polarization, crystallographic methods, neutron scattering, dielectric measurements, thermal, magnetic, and electron paramagnetic resonance (EPR) methods . Optical techniques sensitive to local structural changes such as infrared (IR) and Raman spectroscopy have been carried out on DMMn to investigate the actual microstructural mechanism involved . All these earlier studies had laid emphasis on the response of the high‐wavenumber internal modes across the transition temperatures.…”
Section: Introductionmentioning
confidence: 99%